2007
DOI: 10.1038/sj.npp.1301648
|View full text |Cite
|
Sign up to set email alerts
|

Context-Specific Reversal of Cocaine Sensitization by the CB1 Cannabinoid Receptor Antagonist Rimonabant

Abstract: The CB 1 cannabinoid receptor is implicated in the rewarding properties of many drugs of abuse, including cocaine. While CB 1 receptor involvement in the acute rewarding properties of cocaine is controversial, CB 1 antagonists such as SR141716 (rimonabant) have clearly been found to prevent cue-and cocaine-elicited reinstatement of cocaine self-administration in rodents. Here we demonstrate the novel involvement of CB 1 receptors in the maintenance of behavioral sensitization to cocaine in C57BL/6 mice. Consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 83 publications
(161 reference statements)
5
35
1
Order By: Relevance
“…This finding indicates that the induction or development of motor sensitization is normal if the CB 1 R ligand rimonabant is infused into the NAc, but the expression of cocaine's sensitization is impaired if NAc CB 1 -mediated neurotransmission is modified by rimonabant during this time period. The data are in agreement with previous results using systemic rimonabant because its injection does not affect the development of cocaine's sensitization (Lesscher et al 2005), but expression of behavioral sensitization is impaired (Filip et al 2006;Gerdeman et al 2008). Rimonabant effects could be accounted for by antagonism or inverse agonism of CB 1 R. In this context, Thiemann et al (2008a, b) have observed that AM251, an antagonist of CB 1 receptors, attenuates amphetamine-induced behavioral sensitization.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding indicates that the induction or development of motor sensitization is normal if the CB 1 R ligand rimonabant is infused into the NAc, but the expression of cocaine's sensitization is impaired if NAc CB 1 -mediated neurotransmission is modified by rimonabant during this time period. The data are in agreement with previous results using systemic rimonabant because its injection does not affect the development of cocaine's sensitization (Lesscher et al 2005), but expression of behavioral sensitization is impaired (Filip et al 2006;Gerdeman et al 2008). Rimonabant effects could be accounted for by antagonism or inverse agonism of CB 1 R. In this context, Thiemann et al (2008a, b) have observed that AM251, an antagonist of CB 1 receptors, attenuates amphetamine-induced behavioral sensitization.…”
Section: Discussionsupporting
confidence: 87%
“…The NAc expresses CB 1 R, as reported by Pickel et al (2004) and was confirmed in our lab (MartĂ­n et al 2008). As regards to sensitization to cocaine, cannabinoid CB 1 R in the NAc appear to be involved in the persistence of cocaine addiction (Wiskerke et al 2008), affecting the expression, not induction, of sensitization (Lesscher et al 2005;Filip et al 2006;Gerdeman et al 2008). …”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Full pharmacological antagonism of CB1 decreases the influence of conditioned factors on cocaine seeking and on extracellular Glu and DA in the NAc (CaillĂ© and Parsons, 2006;Cheer et al, 2007;Oleson and Cheer, 2012;De Vries et al, 2001;Xi et al, 2006), as well as expression of cocaine-induced behavioral sensitization in a context-specific manner (Gerdeman et al, 2008). Differently, full pharmacological blockade or complete genetic deletion of CB1 does not affect, or only marginally affect (Chaperon et al, 1998;Soria et al, 2005), the primary reinforcing (Cossu et al, 2001;De Vries et al, 2001;CaillĂ© and Parsons, 2006) and rewarding properties of cocaine (Houchi et al, 2005;Martin et al, 2000), as well as the underlying DA and GABA mechanisms (CaillĂ© and Parsons, 2006;Soria et al, 2005;De Vries and Schoffelmeer, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are other studies that show the contrary (Li et al 2009 ;Soria et al 2005 ;Xi et al 2008). CB 1 receptors appear to be involved in the association of cocaine reward with environmental cues, reinstatement of cocaine self-administration and acquisition of behavioural sensitization (Adamczyk et al 2012 ;de Vries et al 2001 ;Gerdeman et al 2008). Additionally, a new role for cannabinoid CB 2 receptors in cocaine addiction is emerging (Xi et al 2011).…”
Section: Discussionmentioning
confidence: 94%